2013
DOI: 10.15288/jsad.2013.74.361
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on God, Prayer, and Religion Reduces Influence of Perceived Norms on Drinking

Abstract: ABSTRACT. Objective: Previous research has shown that perceived social norms are among the strongest predictors of drinking among young adults. Research has also consistently found religiousness to be protective against risk and negative health behaviors. The present research evaluates the extent to which reliance on God, prayer, and religion moderates the association between perceived social norms and drinking. Method: Participants (n = 1,124 undergraduate students) completed a cross-sectional survey online, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
3
17
0
2
Order By: Relevance
“…Students who choose to attend religiously affiliated institutions might place a higher level of importance on religious beliefs than students at other institutions, and researchers have found that adolescents who attend religious services weekly are less likely to have ever gambled than participants who attend religious services less often (Uecker and Stokes 2015). Similar results have been found when examining religion and alcohol use among college students, as previous research indicates that students' perceived importance of religion is negatively correlated with alcohol consumption (Neighbors et al 2013). While the proportion of past year gamblers in this sample was relatively low, the proportion of our sample that experienced one or more gambling-related problem in the past year (5.1 %) is relatively consistent with proportions found in other studies using college student convenience samples.…”
Section: Discussionsupporting
confidence: 64%
“…Students who choose to attend religiously affiliated institutions might place a higher level of importance on religious beliefs than students at other institutions, and researchers have found that adolescents who attend religious services weekly are less likely to have ever gambled than participants who attend religious services less often (Uecker and Stokes 2015). Similar results have been found when examining religion and alcohol use among college students, as previous research indicates that students' perceived importance of religion is negatively correlated with alcohol consumption (Neighbors et al 2013). While the proportion of past year gamblers in this sample was relatively low, the proportion of our sample that experienced one or more gambling-related problem in the past year (5.1 %) is relatively consistent with proportions found in other studies using college student convenience samples.…”
Section: Discussionsupporting
confidence: 64%
“…Ruiz, González, Vera, & Azancot, (2011) also found that religion can act as a protective factor among the university population against health and nutritional behaviour and habits. Similar results have been described in other countries with a university population of different religious denominations (El Ansari, Sebena & Stock, 2014;Neighbors et al, 2013). However Tanton, Dodd, Woodfield, & Mabhala, (2015) found different result.…”
Section: Discussionsupporting
confidence: 83%
“…This theoretical framework has a lineage that can be traced to George Herbert Mead and that was extended, first by Sutherland () and then by Akers (, ). Scholars who have used SLT to improve our understanding of alcohol use include Neighbors, Brown, DiBello, Rodriguez, and Foster (); Ward and Grycynski (); Varvil‐Weld, Mallett, Turrisi, Cleveland, and Abar (); and Wood, Sher, Erickson, and DeBord (). Social learning theory contends that peer groups help to create social norms.…”
Section: Introductionmentioning
confidence: 99%